2020
DOI: 10.1007/s10140-020-01865-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on emergency department CT for suspected diverticulitis

Abstract: Purpose This study examined the impact of the COVID-19 pandemic on emergency department CT use for acute nontraumatic abdominal pain, to better understand why imaging volume so drastically decreased during the COVID-19 pandemic. Methods This was a retrospective review of emergency imaging volumes from January 5 to May 30, 2020. Weekly volume data were collected for total imaging studies, abdominopelvic CT, and abdominopelvic CTs positive for common causes of acute nontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…Imaging ordering trends in our study were similar to those in others that reported overall decreased imaging utilization mirroring decreased patient census [ 16 , 18 ]. However, we did not find any increase in the utilization of CT to diagnose acute appendicitis during the pandemic, as was reported by Romero et al [ 19 ], whose study included adult and pediatric patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Imaging ordering trends in our study were similar to those in others that reported overall decreased imaging utilization mirroring decreased patient census [ 16 , 18 ]. However, we did not find any increase in the utilization of CT to diagnose acute appendicitis during the pandemic, as was reported by Romero et al [ 19 ], whose study included adult and pediatric patients.…”
Section: Discussionsupporting
confidence: 87%
“…Imaging trends in acute appendicitis have not been as thoroughly studied. A few authors have reported decreased numbers of emergent CTs ordered out of the emergency department (ED) during the pandemic but with a higher proportion of positive findings and more advanced stages of disease [ 16 18 ]. A study by Romero et al [ 19 ] is the only one in the radiology literature to focus on imaging trends in acute appendicitis during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A decline in the use of diagnostic imaging in the ED setting during the pandemic, particularly cross-sectional imaging, has also been documented. Studies have shown a significant decrease in the utilization of ED head CT examinations [ 13 ], abdominopelvic CT examinations [ 14 ], and overall ED imaging [ 15 ] in North American institutions during the COVID pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is less than the change in volume of ED ultrasounds performed by the radiology department, which neared a 60% decline. The relative decrease in utilization of radiology department ultrasound during the pandemic was certainly accentuated by the change in distribution of clinical presentations to the ED [28] and in practitioner decisions to defer imaging of lower acuity patients [14,29]. Another factor leading to our decreased ED imaging utilization in 2020 can be understood by the study population we serve.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, admissions for acute diverticulitis decreased by 56%, from 749 in pre-lockdown to 332 during lockdown. A higher percentage reduction (up to 67%) was observed in the largest series[ 11 , 12 , 14 , 16 , 17 ]. A 4%-8% decrease in the rate of uncomplicated diverticulitis (defined as localized diverticular inflammation without any abscess or perforation) was also noted during the lockdown phase in the three studies from United States.…”
Section: Resultsmentioning
confidence: 90%